2010
DOI: 10.5483/bmbrep.2010.43.8.524
|View full text |Cite
|
Sign up to set email alerts
|

New understanding of glucocorticoid action in bone cells

Abstract: Glucocorticoids (GCs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 51 publications
(32 reference statements)
1
16
0
Order By: Relevance
“…Adipose tissue is the place of secretion of adipokines that influence the metabolic, skeletal, and cardiovascular systems [35]. Bone cells have several specific hormone receptors and can be regarded as a hormone target organ [36,37]. At the same time, OC has been proved to be a factor that may have an effect on body mass control and glucose metabolism [38].…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue is the place of secretion of adipokines that influence the metabolic, skeletal, and cardiovascular systems [35]. Bone cells have several specific hormone receptors and can be regarded as a hormone target organ [36,37]. At the same time, OC has been proved to be a factor that may have an effect on body mass control and glucose metabolism [38].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike, however, the histomorphometry results from the pediatric patients with nephrotic syndrome, our subjects did not have evidence of osteomalacia, as seen by the reduced osteoid thickness and volume. The primary effect of the glucocorticoid treatment in our subjects would appear to be through the reduction in bone formation decreasing osteoblastogenesis, increasing osteoblast apoptosis and inhibiting osteoblast production of bone matrix [3638]. …”
Section: Discussionmentioning
confidence: 99%
“…(52) It has been reported that bone loss occurs with a rapid phase of about 12% within the first year of glucocorticoid administration, followed by a slow phase of 2-5% annually. (53-55) Multiple practice guidelines have been written recommending treatment protocols for patients, including those diagnosed with DMD who are placed on chronic glucocorticoid treatment, to reduce fractures and the morbidity associated with glucocorticoid-induced osteoporosis (see Table 1 and 2). (56-57)…”
Section: Determinants Of Bone Massmentioning
confidence: 99%